Urinary Extracellular Vesicles and Their miRNA Cargo in Patients with Fabry Nephropathy - Levstek, Tina (Genes (Basel), 2021)
Current biomarkers of Fabry nephropathy lack sensitivity in detecting early kidney damage and do not predict progression of nephropathy. Urinary extracellular vesicles (uEVs) and their molecular cargo could reflect early changes in renal impairment as they are secreted by the cells lining the urinary tract. We aimed to conduct a proof-of-concept study to investigate whether analysis of uEV characteristics and expression of uEV-derived microRNAs (miRNAs) could be applicable in studies to predict the development and progression of nephropathy in Fabry disease. A total of 20 Fabry patients were divided into two groups, depending on the presence of nephropathy. Chronological urine samples collected during 10-year follow-up were used for uEVs isolation with size exclusion chromatography. Nanoparticle tracking analysis was used to determine concentration and size of uEVs. We evaluated the expression of five uEV-derived miRNAs by qPCR (miR-23a-3p, miR-29a-3p, miR-30b-5p, miR-34a-5p, miR-200a-3p). There was no difference in the concentration and size of uEVs between patients with and without nephropathy at last follow-up or longitudinally. However, we found increased expression of miR-29a-3p and miR-200a-3p in uEVs isolated from chronological samples of patients with Fabry nephropathy. This may indicate an attempt by the organism to prevent the progression of renal damage leading to end-stage renal disease as previously reported in type 1 diabetes. In addition, we found an increased expression of miR-30b-5p in the 10-year period in uEVs of patients without renal dysfunction. miR-30b-5 was reported to have a protective role in podocyte injury and may possibly be important in Fabry nephropathy. These findings indicate that uEVs and their molecular cargo could be a promising target of studies focusing on elucidation of Fabry nephropathy. Nevertheless, total concentration and size of uEVs were neither indicative of the presence nor progression of Fabry nephropathy, while the role of the analyzed miRNAs in Fabry nephropathy progression was merely indicated and needs further in-depth studies.